Proceedings of 10th International Kimberlite Conference Volume 2 - Pearson, D Graham.; Pearson, D Graham.; Grütter, Herman S.; Grütter, Herman S.; Harris, Jeff W.; Harris, Jeff W.; Kjarsgaard, Bruce A.; Kjarsgaard, Bruce A.; O’Brien, Hugh.; O’Brien, Hugh.; Rao, N V Chalapathi.; Rao, N V Chalapathi.; et al. (Springer India : Imprint: Springer, 2013)
International Kimberlite conferences (IKCs) are special events that are held across the world once in four to five years. IKC is the confluence platform for academicians, scientists and industrial personnel concerned with diamond exploration and exploitation, petrology, geochemistry, geochronology, geophysics and origin of the primary diamond host rocks and their entrained xenoliths and xenocrysts (including diamond) to get together and deliberate on new advances in research made in the intervening years. Ever since the organization of first IKC in 1973 and its tremendous success, the entire geological world eagerly look forward to subsequent such conferences with great enthusiasm and excitement. The scientific emanations from IKCs continue to make significant impact on our understanding of the composition, nature and evolution of the planet we live on. The previous conferences were held at Cape Town (1973), Santa Fe, New Mexico (1977), Clermont-Ferrand, France, (1982). Perth, Western Australia (1987), Araxa, Brazil (1991), Novosibirsk, Russia (1995), Cape Town (1998), Victoria, Canada (2003) and Frankfurt, Germany (2008). The tenth IKC was held at Bangalore, India between 5th and 11th February 2012. The conference was organized by the Geological Society of India in association with the government organizations, academic institutions and Indian diamond mining companies. About 300 delegates from 36 countries attended the conference and 224 papers were presented. The papers include 78 oral presentations and 146 poster presentations on following topics: Kimberlite geology, origin, evolution and emplacement of kimberlites and related rocks, petrology and geochemistry of metasomatised lithospheric mantle magmas, diamond exploration, cratonic roots, diamonds, diamond mining and sustainable developments and policies and governance of diamond exploration. Pre- and post-conference field trips were organized to (i) the diamond bearing kimberlites of Dharwar Craton in south India, (ii) lamproites of Bundelkhand Craton in northern India and (iii) diamond cutting and polishing industry of Surat, Gujarat in western India. A series of social and cultural programmes depicting cultural diversity of India were organized during the conference. The Kimberlite fraternity enjoyed yet another socially and scientifically successful conference.  .